"A General Separation of Colored and White": The WWII Riots, Military Segregation, and Racism(s) beyond the White/Nonwhite Binary. Issue 4 (October 2015) - Aragon, Margarita
This article uses archival research to explore important differences in the discursive and institutional positioning of Mexican American and African American men during World War II. Through the focal point of the riots that erupted in Los Angeles and other major cities in the summer of 1943, I examine the ways in which black and Mexican "rioters" were imagined in official and popular discourses. Though both groups of youth were often constructed as deviant and subversive, there were also divergences in the ways in which their supposed racial difference was discursively configured. I also consider the experiences of each group in the World War II military, a subject that has received little attention in previous work on the riots. Though both groups were subject to discrimination and brutality on the home front, only African Americans were segregated in the military—a fact that profoundly influenced the 1943 riots. Examining the very different conditions under which these men served, as well as the distinct ways in which their presence within the military and on the home front was interpreted and given meaning by press, law enforcement, and military officials, helps to illuminate the uneven and complex workings of racism in America, disrupting the common conceptualization of a definitive white/nonwhite color line.